Anticancer potential of Amaryllidaceae alkaloids evaluated by screening with a panel of human cells, real-time cellular analysis and Ehrlich tumor-bearing mice - Havelek, Radim; Muthna, Darina; Tomsik, Pavel; Královec, Karel; Seifrtova, Martina; Cahlikova, Lucie; Hostalkova, Anna; Safratova, Marcela; Perwein, Maria; Cermakova, Eva; Rezacova, Martina (Elsevier Ireland Ltd, 2017)
In this study, twenty-two Amaryllidaceae alkaloids were screened for their anticancer potential. All isolates were evaluated for antiproliferative activities on a panel of 17 human cell types of different tissue origin using WST-1 assay. In addition, we determined the antiproliferative effect with a real-time cell analysis xCELLigence system. Thereafter, to evaluate the barely known in vivo anticancer potential of the most potent molecule haemanthamine, a preliminary study was performed using an Ehrlich tumor-bearing mice model. The results showed that haemanthamine, lycorine and haemanthidine exerted the highest antiproliferative activity. The mean growth percent (GP) value after a single-dose 10 mu M treatment was for haemanthamine 21%, for lycorine 21% and for haemanthidine 27% that of untreated control cells (100%). Furthermore, haemanthamine, lycorine and haemanthidine exhibited significant cytotoxicities against all the tested cell lines with individual IC50 values in the micromolar range. Dynamic real-time measures of impedance by xCELLigence indicated that these three compounds suppress cell proliferation after 10 h of treatment at a concentration of 10 mM or higher. Regrettably, in a follow-up in vivo antitumor activity study, haemanthamine showed no statistically significant reduction in the tumor size with no prolongation of survival time of Ehrlich tumor-bearing mice. Taken together, these results provide a new clue and guidance for exploiting Amaryllidaceae alkaloids as anticancer agents.
Protinádorový potenciál alkaloidů čeledi Amaryllidaceae testovaný na panelu lidských linií, pomocí analýzy buněk v reálném čase a na Ehrlichově nádoru myší
Keywords: Antiproliferative activity; Amaryllidaceae; Alkaloids; In vitro; In vivo; Antiprolifeační aktivita; Amaryllidaceae; Alkaloidy; In vitro; In vivo